Estimate the relationship between CXCR4-SDF-1 axis and inhibitory molecules (CTLA4 and PD-1) in patients with colon cancer - Abdul-Huseen, Suhad D.; Alabassi, Hazima M. (Narra J, 2024)
Colon neoplasia is one of the major malignancies in industrialized countries due to their Western-style food habits. It accounts for more than 50% of the population developing adenomatous polyps by the age of 70 years, but 10% of cancers in developed countries. The aim of this study was to evaluate the pathological role of the C-X-C chemokine receptor type 4/stromal-derived factor 1 axis (CXCR4-SDF-1  axis), and the inhibitory molecules PD-1 and cytotoxic T-lymphocyte associated protein 4 (CTLA-4) in postoperative colon cancer patients undergoing treatment with chemotherapy (oxaliplatin and capecitabine) and estimate the correlation between these studied factors to deeply understand the basic mechanisms and potential diagnostic or therapeutic effects. The study involved 90 patients, including 50 colon cancer patients (male and female, aged 35–65) diagnosed by oncologists at Al-Ramadi Hospital, Ramadi, Iraq. All patients underwent surgical resection and received four cycles of chemotherapy with oxaliplatin (85 mg every 21 days) and capecitabine (6 grams daily for 21 days). Additionally, 40 age- and sex-matched individuals served as the control group. For each participant, CXCR4 and SDF-1 levels were measured using ELISA and the gene expression of CTLA-4 and PD-1 were measured using RT-PCR. The colon cancer patient group showed significantly lower levels of CXCR4 and SDF-1 compared to control groups (0.163±0.012 vs 0.376±0.025 pg/mL and 0.376±0.025 vs 0.699±0.110 pg/mL, respectively, both had p=0.001). Moreover, the colon cancer patient group had significantly lower expression of PD-1 and CTLA4 compared to control group (0.102±0.029-fold vs 1.199±0.391-fold, p=0.02; and 0.302±0.140-fold vs 1.441±0.334-fold, p=0.008, respectively). In conclusion, the results suggest that CXCR4 and SDF-1 appear promising as diagnostic markers for distinguishing colon cancer patients from healthy conditions.